How integrated are neurology and palliative care services? Results of a multicentre mapping exercise - van Vliet, Liesbeth M.; Gao, Wei; DiFrancesco, Daniel; Crosby, Vincent; Wilcock, Andrew; Byrne, Anthony; Al-Chalabi, Ammar; Chaudhuri, K. Ray; Evans, Catherine; Silber, Eli; Young, Carolyn; Malik, Farida; et al. (BioMed Central, 2016)
Background: Patients affected by progressive long-term neurological conditions might benefit from specialist palliative care involvement. However, little is known on how neurology and specialist palliative care services interact. This study aimed to map the current level of connections and integration between these services. Methods: The mapping exercise was conducted in eight centres with neurology and palliative care services in the United Kingdom. The data were provided by the respective neurology and specialist palliative care teams. Questions focused on: i) catchment and population served; ii) service provision and staffing; iii) integration and relationships. Results: Centres varied in size of catchment areas (39-5,840 square miles) and population served (142,000-3,500,000). Neurology and specialist palliative care were often not co-terminus. Service provisions for neurology and specialist palliative care were also varied. For example, neurology services varied in the number and type of provided clinics and palliative care services in the settings they work in. Integration was most developed in Motor Neuron Disease (MND), e.g., joint meetings were often held, followed by Parkinsonism (made up of Parkinson’s Disease (PD), Multiple-System Atrophy (MSA) and Progressive Supranuclear Palsy (PSP), with integration being more developed for MSA and PSP) and least in Multiple Sclerosis (MS), e.g., most sites had no formal links. The number of neurology patients per annum receiving specialist palliative care reflected these differences in integration (range: 9–88 MND, 3–25 Parkinsonism, and 0–5 MS). Conclusions: This mapping exercise showed heterogeneity in service provision and integration between neurology and specialist palliative care services, which varied not only between sites but also between diseases. This highlights the need and opportunities for improved models of integration, which should be rigorously tested for effectiveness.